Development of non-occlusive blood pressure monitor with height correction for home used application - Agung W. Setiawan; Nur A. Heryanto; Fadel M. Putra; Febri Suyitno; M. Andre Martin; Yana S. Raharja (Institute of Advanced Engineering and Science, 2019)
Non-occlusive blood pressure measurement method is developed to avoid the use of discontinuous and uncomfortable cuff-based methods. In this research, Pulse Transit Time (PTT) and Photoplethysmogram Intensity Ratio (PIR) is used to measure blood pressure. Two photoplethysmogram (PPG) sensors that are placed on the wrist and one of the finger joints both on the left hand is used to get the PTT and PIR. The name of the device is ARTSEN. During measurement, there is a measurement error caused by the hydrostatic effect when the device position is not inline with the heart. To minimize this error, this research proposes an automatic continuous blood pressure monitor. The device will conduct measurement only when the height of the device is inline with the heart. Accelerometer and gyroscope are used to detect the height of the device. There are 30 subjects that are involved in this research. To evaluate the performance of the device, there are two measurement conditions, during lying in the bed and sit down position. The blood pressure measurement is conducted using ARTSEN and sphygmomanometer (as the gold standard of blood pressure measurement). The average error of systolic blood pressure is 8 mmHg with standard deviation 5 mmHg, and average error of diastolic blood pressure is 8 mmHg with standard deviation 4 mmHg.